The need for a universal model agreement under International Law Commission (ILC) for development of shared oil and gas resources - Ahmad Kashfi,; Wan Siti Adibah Wan Dahalan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper embarks on rationalizing the significance of codification of a convention for development of shared oil and gas resources under the supervision by International Law Commission (ILC). Transboundary natural resources would be discovered increasingly by development of technology that helps the States to exploit in any region and depth, and in adverse circumstances. The legal intricacies affecting such resources under international law originates from some significant factors such as complexity of oil and gas ownership, lack of international organization, association or convention to directly enforce the related rules for or against the States. Moreover, the States’ practice to cooperate through agreements are operationalised through various frameworks in different regions in the world. They are inconsistencies in the structure, provisions and regime of application due to their national interests, economic systems and goals and historical and political backgrounds. This paper reviews the relevant international law sources in an analytical and explanatory method and a theoretically doctrinal way to prove the reason why codification of a comprehensive model agreement in International Law Commission (ILC) would be the most efficient way to overcome such legal intricacies and lack of relevant international law rules. The significance and necessity of a universally binding convention is justified through this paper. The predominant provisions and main principles that can be included in the model agreement as a potential annex to the convention are illustrated, along with the applicability of the codification of both convention and a model agreement in the International Law Commission (ILC).